Preparation and use of MitoPY1 for imaging hydrogen peroxide in mitochondria of live cells - Dickinson, Bryan C (2013)
Mitochondria peroxy yellow 1 (MitoPY1) is a small-molecule fluorescent probe that selectively tracks to the mitochondria of live biological specimens and responds to local fluxes of hydrogen peroxide (H(2)O(2)) by a turn-on fluorescence enhancement. This bifunctional dye uses a triphenylphosphonium targeting group and a boronate-based molecular switch to selectively respond to H(2)O(2) over competing reactive oxygen species (ROS) within the mitochondria. MitoPY1 can be used to measure mitochondrial H(2)O(2) levels in both cell culture and tissue models. In this protocol, we describe the synthesis of MitoPY1 and how to use this chemical tool to visualize mitochondrial H(2)O(2) in live cells. The preparation of MitoPY1 is anticipated to take 7–10 d, and assays involving microscopy of cultured mammalian cells can be performed in 1–2 d.